STRATEGIES FOR DEVELOPING THE ISLAMIC MARKET IN THE DIGITAL ERA TO SUPPORT THE SHARIA ECONOMY - Eni Khasanatun Nisa (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
This study aims to identify strategies for developing the Islamic market in the digital era to support the growth of the sharia economy. Using a literature review method, the research explores various strategies applicable to Islamic markets, including the utilization of digital platforms, promotion of halal products, and collaboration with sharia fintech. Data were collected from secondary sources, including scholarly articles, research reports, relevant regulations, and literature related to the sharia economy.The findings reveal that digitalization provides significant opportunities for Islamic markets to enhance accessibility and service efficiency for Muslim consumers. However, challenges remain, such as limited digital infrastructure and low technological literacy among MSME actors. The study concludes that optimal implementation of digital technology, accompanied by education and collaboration with sharia financial institutions, can strengthen the Islamic market's contribution to the sharia economy. Recommendations are provided for the government, business actors, and related institutions to improve infrastructure and support digital literacy to maximize the potential of the Islamic market in Indonesia.